Return of a Fragile X Syndrome Genetic Result: Exploring the feedback of Individual genetic findings and their relation to traditional knowledge in a village in Cameroon - Karen, Kengne Kamga (Division of Human Genetics, 2022)
Introduction: Fragile X Syndrome (FXS) is the most common genetic cause of intellectual disability (ID) and Autism Spectrum Disorder (ASD). It is caused by the expansion of CGG (Cytosine, Guanine, Guanine) repeats at the 5' untranslated region (UTR) of the Fragile X Mental Retardation gene 1 (FMR1). This gene codes for the Fragile X Mental retardation protein, which is responsible for healthy brain development. This condition is transmitted through an X-linked dominant pattern and is known to affect approximately 1 in 2500–4000 males and 1 in 7000–8000 females. In 2011, two siblings received a positive diagnosis of FXS at the Child Neurology Unit of the Yaoundé Gynaeco-Obstetric and Paediatric hospital in Cameroon. Informal data from the first consultation with their mother (P0), showed that she related her children's condition to a curse from her maternal grandfather, the village's chief. This prompted us to ask four research questions for this project: What is the transmission pattern for FXS in this family? How do families and communities explain the pattern of FXS and other inherited forms of ID in the village? What is the impact of receiving a genetic diagnosis on individuals, families, and communities? And what are the stigma experiences around FXS in this community? As a first step to gather empirical work, a scoping review of the lived experiences of FXS caretakers was conducted. It was revealed that these experiences could broadly be summarised into four main themes, namely: grief experiences, challenges of living with FXS, coping mechanisms, and the need to plan for the future of children with FXS. From this review, it was noted that healthcare workers had limited knowledge and a lack of expertise regarding FXS, whilst there was an overall lack of African qualitative literature on FXS. This set the precedent for the second and third components of the project. Methodology: An ethnographic approach was used in this study. Snowball sampling was used to recruit 92 participants who were 18 years old and above. A topic guide was used to gather data through 10 focus group discussions and 23 in-depth interviews with NVivo 12 used for data analysis. The questionnaire explored participants' understanding of FXS, their lived experiences, the stigma association with FXS, and the effects of receiving a positive or negative genetic diagnosis. Moreover, cascade counselling and testing for FXS was offered to 46 participants. Data gathered from this component was analysed using Epi-info 7.2. and pedigrees were drawn using Cyrillic 3.0.400. Results & Discussion: Cascade testing included 58% of participants (n = 27/46) that were females. The FXS laboratory diagnosis of females showed 14.81% (n = 4/27) with a full mutation, 37.04% (n = 10) had a premutation and 48.15% (n = 13/27) were normal. On the other hand, 21.05% (n=4/19) males had a full mutation. The analysis of this family's pedigree further revealed that the founder of this family was probably a normal transmitting male carrier. Moreover, people in the community and this family described the causes of FXS or inherited forms of ID in four different explanatory models. The curse model was the primary explanatory model and is based on a curse from the chief who bewitched his daughters and wives because they did not mourn his ID servant. Other explanations were the spiritual model that relates FXS to a punishment from God and the psychosocial model, which attributes FXS to events in the prenatal and perinatal periods. Finally, the genetic model is an emerging explanation resulting from the return of the FXS genetic result. Furthermore, receiving a genetic diagnosis resulted in two main themes which were psychological adaptation and communication of the genetic risk of FXS. Receiving a diagnosis was associated with happiness and relief, while the latter described genetic guilts, survivor guilt, and frustrations associated with a family history of FXS and taking care of developmentally delayed children. Lastly, in this community, we identified public stigma directed towards the royal family and courtesy stigma experienced by the royal family members. Most interviewees believed that people from the royal family should have a unique way of addressing FXS children from the chieftaincy because of their position in society. Due to their social position, the royal family uses their status to negotiate marriages with community members. Conclusion: Early detection of carrier status will increase family planning options through genetic counselling, premarital screening, and prenatal diagnosis. My findings identified specific sociocultural challenges that should be addressed during the development and implementation of genetic counselling services. Returning the result of a genetic test can create feelings of guilt in the patient and their relatives. Over time, these families can develop coping mechanisms that revolve around preparing future generations about the risk of having FXS. Hence, health care workers or people who are comfortable talking about FXS should serve as intermediaries for affected families.